Design and Analysis of Fused Deposition Modeling 3D Printer Nozzle for Color Mixing. (13th August 2017) - Han, Shanling; Xiao, Yu; Qi, Tao; Li, Zhiyong; Zeng, Qingliang
Abstract : Fused deposition modeling (FDM) has been one of the most widely used rapid prototyping (RP) technologies leading to the increase in market attention. Obviously it is desirable to print 3D objects; however, existing FDM printers are restricted to printing only monochrome objects because of the entry-level nozzle structure, and literature on the topic is also sparse. In this paper, the CAD model of the nozzle is established first by UG (Unigraphics NX) software to show the structure of fused deposition modeling 3D printer nozzle for color mixing. Second, the flow channel model of the nozzle is extracted and simplified. Then, the CAD and finite element model are established by UG and ICEM CFD software, respectively, to prepare for the simulation. The flow field is simulated by Fluent software. The nozzle's suitable temperature at different extrusion speeds is obtained, and the reason for the blockage at the intersection of the heating block is revealed. Finally, test verification of the nozzle is performed, which can produce mixed-color artifacts stably.